2012
DOI: 10.1136/jech-2012-201081
|View full text |Cite
|
Sign up to set email alerts
|

Learning about scale, measurement and community mobilisation: reflections on the implementation of the Avahan HIV/AIDS initiative in India

Abstract: Debates have raged in development for decades about the appropriateness of participatory approaches and the degree to which they can be managed, scaled and measured. The Avahan programme confronted these issues over the last 7 years and concludes that it is advantageous to manage scaled community mobilisation processes so that participation evolves and programming on the ground is shaped by what is learnt through implementation. The donor (Bill & Melinda Gates Foundation) and its partners determined a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…Community mobilisation and structural intervention strategies have been an integral component of the Avahan initiative for HIV prevention efforts in four southern states of India 12. These initiatives have incorporated the main lessons from the Sonagachi experience, so that these programmes, including our project, can be looked on as further testing of the applicability of the Sonagachi model.…”
Section: Study Settingmentioning
confidence: 99%
“…Community mobilisation and structural intervention strategies have been an integral component of the Avahan initiative for HIV prevention efforts in four southern states of India 12. These initiatives have incorporated the main lessons from the Sonagachi experience, so that these programmes, including our project, can be looked on as further testing of the applicability of the Sonagachi model.…”
Section: Study Settingmentioning
confidence: 99%
“…17 From a community mobilisation perspective, India has an extensive history of successful participatory development approaches, ranging from longstanding production cooperatives to large self-help group movements. 22 The Sonagachi project in Kolkata, West Bengal, is a globally recognised model of a community-led FSW intervention resulting in both HIV risk reduction and improved social outcomes. 23 HIV prevention interventions among FSWs, MSM and TGs, however, were hampered by legal issues, pervasive stigma and discrimination, including from health providers and by social stratification.…”
Section: The Indian Contextmentioning
confidence: 99%
“…First, to support community ownership and social norm change, a progressively participatory approach was implemented whereby KPs were encouraged and capacitated to shape, refine and implement the program. 22 Second, to support management and performance measurement, a common minimum program was developed to set minimum standards, which were periodically and iteratively improved and expanded. Routine data collection systems were established to aggregate and consolidate indicators at every level, from the frontline workers through to KP-program contact points to district, stage and central levels.…”
Section: Implementation Approach To Avahan's Scale-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The Avahan program's focus on building the organizational capacity of most-at-risk populations has been described elsewhere. 30 The prior experience of large donor-funded programs in India indicated that transition to country ownership also required strengthening the government's capacity to absorb and manage the new program. 14 Building on the work of Eric Goosby and colleagues 4 and of Adrienne Germain, 6 we identified four dimensions critical to the sustainability of donor programs through increased country ownership.…”
Section: A Transition Framework For Sustainabilitymentioning
confidence: 99%